Breakage-resistant photoelectric composite cable for wiring in narrow space
By using spherical rare earth nanomaterials and stannate-bound crosslinked polyethylene materials in the protective layer of the photoelectric composite cable, the problems of flammable and compressive performance of the photoelectric composite cable in a narrow space are solved, and flame retardant heat stability is achieved and both performance and pressure and fracturing resistance.
Patent Information
- Application Number
- CN202510001358.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Optoelectronic composite cables wired in narrow spaces are prone to combustion due to heat accumulation, and the prior art is difficult to take into account both flame retardant and compressive resistance.
Use cerium nitrate and other rare earth metal-containing compounds to prepare spherical rare earth nanomaterials and combine them with stannate to serve as the matrix of the protective layer of composite crosslinked polyethylene cables. The cable is improved by combining crosslinked polyethylene materials with spherical rare earth nanomaterials. Thermal stability and compressive resistance.
The dual functions of flame retardant thermal stability and pressure resistance and fracturing resistance of photoelectric composite cables are realized, reducing the diameter and volume of the cable, reducing the risk of mechanical stress and compression, and improving the overall performance of the cable.
Smart Images

Figure CN119391069A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable preparation, and in particular to a photoelectric composite cable that is break-resistant and can be wired in a narrow space. Background Art
[0002] Optical fiber composite cable is a cable that integrates optical fiber and power transmission line. This cable combines the advantages of optical fiber communication and the function of power transmission. It is suitable for scenarios where data transmission and power supply are required at the same time. It usually consists of the following parts: optical fiber unit: used to transmit high-speed data signals, usually single-mode or multi-mode optical fiber; conductive core: used to transmit power, generally made of conductive materials such as copper or aluminum; external protective layer: provides mechanical protection and weather resistance. At present, optical fiber composite cables are widely used in smart grids, communication base stations, transportation facilities, industrial automation and smart homes. In scenarios such as smart homes and smart factories, optical fiber composite cables are usually integrated together for wiring due to the requirements of the degree of integration, thereby saving space and ceding space to large equipment to the greatest extent. Therefore, optical fiber composite cables often need to be wired in small spaces.
[0003] In the optoelectronic composite cable, there is both power transmission and data transmission, and the power line will generate heat. In a small space, the air circulation is poor, which can easily lead to heat accumulation and even combustion. Therefore, the optoelectronic composite cable is required to have good flame retardant properties. For example, the invention patent with the publication number CN114276608A discloses a halogen-free flame retardant and heat-resistant cable material, which uses silicon dioxide and thermoplastic polyurethane as the shell and ammonium polyphosphate as the core. The ammonium polyphosphate is microencapsulated and modified to improve the heat resistance of the cable material. The present invention provides an optoelectronic composite cable that is resistant to breakage in a small space. Spherical rare earth nanomaterials are prepared using compounds containing rare earth metals such as cerium nitrate, and tin is used to prepare the spherical rare earth nanomaterials. The acid salt is used as a matrix to provide a stable frame structure, which not only improves the heat resistance but also improves the compressive resistance of the cable protective layer material. In this way, the optoelectronic composite cable only needs one protective layer to complete the dual functions of flame retardancy and compression resistance, preventing the diameter and volume of the optoelectronic composite cable from being too large, thereby reducing the extrusion from other equipment and the cable's own structure, and reducing the risk of mechanical stress compression. Therefore, the present invention provides a breakage-resistant optoelectronic composite cable for wiring in a narrow space, and its composite cross-linked polyethylene cable protective layer has both flame retardant thermal stability and pressure resistance and crack resistance to solve the problems existing in the prior art. Summary of the invention
[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a photoelectric composite cable that is resistant to breakage when wiring in a narrow space.
[0005] A photoelectric composite cable that is resistant to breakage when laid in a narrow space, comprising a composite cross-linked polyethylene cable protective layer and an optical cable, wherein the composite cross-linked polyethylene cable protective layer comprises the following components: 16-18% by mass of a precursor powder, 5-6% of a carbonizing agent and 74.6-78% of PE, 0.6-0.8% of triallyl cyanate and 0.4-0.6% of diisopropylbenzene peroxide; a preparation method of the composite cross-linked polyethylene cable protective layer comprises: adding the precursor powder, the carbonizing agent and PE to an internal mixer, heating and stirring, then adding triallyl cyanate and diisopropylbenzene peroxide, mixing, transferring to a twin-screw extruder, and melt extruding to obtain the composite cross-linked polyethylene cable protective layer; The preparation method of the precursor powder is as follows: 100-110 parts by weight of silica-coated ammonium polyphosphate powder, 2-2.5 parts by weight of triethylamine and 200-205 parts by weight of chloroform are added to a reaction bottle, heated to 45-50° C., stirred at 300-400 r / min for 5-10 minutes, and then 18-24 parts by weight of spherical rare earth nanomaterials and 5.7-6.8 parts by weight of antioxidant are added, reacted for 4-4.5 hours, then cooled to 25° C., filtered, washed the solid product with water and chloroform respectively, and then dried at 80-85° C. for 9-10 hours to obtain the precursor powder; The preparation method of the spherical rare earth nanomaterial comprises: weighing cerium nitrate crystals and yttrium nitrate crystals, dissolving them in deionized water, stirring them evenly with a magnetic force to obtain a mixed solution, weighing sodium stannate trihydrate, adding them to the mixed solution, stirring them magnetically to obtain a mixed ion solution, and mixing the mixed ion solution with concentrated ammonia water, then continuing to stir, heating, centrifuging, collecting precipitates, and drying them to obtain the spherical rare earth nanomaterial; The preparation method of the antioxidant is as follows: 2,6-di-tert-butylphenol and butyl diphenylamine are mixed in a mass ratio of (27-30): (55-65), and then added into an equal mass of n-decane, and then 5-8% of the total mass of the system is added with benzoyl peroxide, and the mixture is heated to 140-180° C. and reacted for 2-3 hours to obtain the antioxidant.
[0006] Furthermore, the method for preparing the composite cross-linked polyethylene cable protective layer comprises the following steps: S1: preparing spherical rare earth nanomaterials: weighing cerium nitrate crystals and yttrium nitrate crystals, dissolving them in deionized water, and stirring them evenly with a magnetic stirrer to obtain a mixed solution, weighing sodium stannate trihydrate, adding them to the mixed solution, and stirring them magnetically to obtain a mixed ion solution, and mixing the mixed ion solution with concentrated ammonia water, and then continuing to stir, heat, centrifuge, collect the precipitate, and dry it to obtain a spherical rare earth nanomaterial; S2: preparing silica-coated ammonium polyphosphate powder: adding ammonium polyphosphate into an ethanol aqueous solution, dispersing, then adding DMDES and TEOS, stirring, reacting to obtain a suspension, filtering the suspension, and drying to obtain silica-coated ammonium polyphosphate powder; S3: Surface treatment of silica-coated ammonium polyphosphate powder: Add silica-coated ammonium polyphosphate powder into a reaction bottle, add anhydrous ethanol and deionized water, and then add silane coupling agent KH-560, stir, then filter to remove the filtrate, wash the solid with anhydrous ethanol, and dry to obtain modified silica-coated ammonium polyphosphate powder; S4: Preparation of composite cross-linked polyethylene cable protective layer: Mix 2,6-di-tert-butylphenol and butyldiphenylamine and add to n-decane, then add benzoyl peroxide and heat to obtain an antioxidant, add modified silica-coated ammonium polyphosphate powder, triethylamine and chloroform to a reaction bottle, heat and stir, then add spherical rare earth nanomaterials and antioxidants, react, filter, wash the solid product, dry to obtain a precursor powder, add the precursor powder, carbon-forming agent and PE to an internal mixer, heat and stir, then add triallyl cyanate and diisopropyl peroxide, mix, transfer to a twin-screw extruder, melt extrude to obtain a composite cross-linked polyethylene cable protective layer.
[0007] Furthermore, the method for preparing the composite cross-linked polyethylene cable protective layer, step S1 of preparing spherical rare earth nanomaterials, comprises the following steps: S1.1: Weigh 99-101 parts by mass of cerium nitrate crystals and yttrium nitrate crystals, dissolve them in 200-250 parts by volume of deionized water, control the molar mass ratio of cerium atoms to yttrium atoms to be (97-98):(2-3), stir magnetically to obtain a mixed solution; S1.2: adding sodium stannate trihydrate to the mixed solution, controlling the molar mass ratio of n(Ce+Y):n(Sn) in the mixed solution to be 1:(1-1.2), magnetically stirring for 10-12 minutes to obtain a mixed ion solution, and stirring at a speed of 1000-1200 r / min, mixing the mixed ion solution with 40-45 parts by volume of concentrated ammonia water under stirring, and then dropping NaOH solution to adjust the pH value to 12-12.5; S1.3: Then continue stirring for 1-1.5 hours and then transfer to a reactor. Use deionized water to adjust the solution volume to 75-80% of the reactor lining volume, and heat to 180-190°C and react for 12-12.5 hours. After the reaction is completed, naturally cool to room temperature 24°C, collect the precipitate by centrifugation, wash it 3 times with deionized water, and then place it in a vacuum drying oven at 100-110°C and dry it for 4-4.5 hours to obtain spherical rare earth nanomaterials.
[0008] Furthermore, the method for preparing the composite cross-linked polyethylene cable protective layer, step S2 preparing silica-coated ammonium polyphosphate powder, comprises the following steps: S2.1: 100-110 parts by weight of ammonium polyphosphate is added to 400-420 parts by weight of ethanol aqueous solution, and dispersed at a speed of 150-200 r / min for 5-10 minutes, and then the pH value is adjusted to 10-10.5 with ammonia water, and then 20-25 parts by weight of DMDES and 20-25 parts by weight of TEOS are added, and stirred at 50-100 r / min for 2-3 minutes, and the temperature is raised to 45-50°C while stirring, and the reaction is carried out for 2-2.5 hours to obtain a suspension; S2.2: The suspension is filtered, and the filter residue is washed with anhydrous ethanol for three times, then placed in a Soxhlet extractor and extracted with anhydrous ethanol for 20-22 hours, and finally placed in an electric heated forced air drying oven at 80-85°C and dried for 20-24 hours to obtain silica-coated ammonium polyphosphate powder.
[0009] Furthermore, in the method for preparing the composite cross-linked polyethylene cable protective layer, step S3 of surface treatment of the silica-coated ammonium polyphosphate powder comprises the following steps: S3.1: Add 65-70 parts by mass of silica-coated ammonium polyphosphate powder into a reaction bottle, add 200-220 parts by volume of anhydrous ethanol and 50-60 parts by volume of deionized water, and then add 0.65-0.7 parts by mass of silane coupling agent KH-560; S3.2: The reaction bottle is then fixed on a mechanical stirrer and reacted at 60-65°C for 1-1.5 hours. The filtrate is then filtered to remove the filtrate. The solid is washed three times with anhydrous ethanol and placed in a drying oven at 80-85°C for 10-12 hours to obtain surface-modified silica-coated ammonium polyphosphate powder.
[0010] Furthermore, the method for preparing the composite cross-linked polyethylene cable protective layer, step S4 of preparing the composite cross-linked polyethylene cable protective layer, comprises the following steps: S4.1: 2,6-di-tert-butylphenol and butyl diphenylamine are mixed in a mass ratio of (27-30):(55-65), and then added to an equal mass of n-decane, and then 5-8% of the total mass of benzoyl peroxide is added, and the mixture is heated to 140-180°C and reacted for 2-3 hours to obtain an antioxidant; S4.2: Add 100-110 parts by weight of silica-coated ammonium polyphosphate powder, 2-2.5 parts by weight of triethylamine and 200-205 parts by weight of chloroform into a reaction bottle, heat to 45-50°C, stir at 300-400 r / min for 5-10 min, then add 18-24 parts by weight of spherical rare earth nanomaterials and 5.7-6.8 parts by weight of antioxidant, react for 4-4.5 h, then cool to 25°C, filter, wash the solid product with water and chloroform respectively, and then dry at 80-85°C for 9-10 h to obtain a precursor powder; S4.3: Add 16-18% by mass of precursor powder, 5-6% of carbonizing agent and 74.6-78% of PE into the internal mixer, heat to 110-120°C, and stir at a speed of 40-60r / min until all melted, then add 0.6-0.8% of triallyl cyanate and 0.4-0.6% of diisopropyl peroxide, and then mix at 160-170°C for 15-20min, transfer to a twin-screw extruder, and melt extrude at a temperature of 180-200°C to obtain a composite cross-linked polyethylene cable protective layer.
[0011] Furthermore, in the method for preparing the composite cross-linked polyethylene cable protective layer, the mass fraction of concentrated ammonia water in step S1.3 is 25-30%.
[0012] Furthermore, in the method for preparing the composite cross-linked polyethylene cable protective layer, the ethanol aqueous solution in step S2.1 is prepared by mixing anhydrous ethanol and deionized water in a mass ratio of 2: (1-1.5).
[0013] Furthermore, in the method for preparing the composite cross-linked polyethylene cable protective layer, the carbon-forming agent in step S4.3 is specifically a triazine macromolecular carbon-forming synergist.
[0014] Furthermore, the preparation method of the photoelectric composite cable that is resistant to being wired in a narrow space is to bundle optical cables into cables and cover them with the composite cross-linked polyethylene cable protective layer to obtain the photoelectric composite cable that is resistant to being wired in a narrow space.
[0015] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The present invention prepares spherical rare earth nanomaterials by compounding cerium nitrate, yttrium nitrate and sodium stannate. The stannate serves as a matrix and provides a stable framework structure, so that cerium and yttrium ions can be evenly distributed therein. At the same time, the high melting point and good chemical stability of the stannate are conducive to forming a stable crystal structure. Cerium and yttrium are both trivalent rare earth ions with similar ion radii. They can replace each other in the lattice to form a solid solution. Therefore, the cerium ions of cerium nitrate, the yttrium ions of yttrium nitrate and sodium stannate can eventually form a crystalline material with a nearly spherical polyhedral structure, thereby improving the mechanical properties of the composite cross-linked polyethylene cable protective layer, making it less likely to delaminate and crack the composite material even when it is under pressure for a long time, and due to the change in its microstructure, the structure becomes denser and its compressive resistance is also improved to a certain extent.
[0016] 2. The present invention compounds the silica-coated ammonium polyphosphate powder with an antioxidant, wherein the antioxidant is prepared by reacting 2,6-di-tert-butylphenol and butyl diphenylamine, and is a phenol antioxidant. The phenol antioxidant can treat silica, thereby inhibiting the oxidation process of silica at high temperatures and improving thermal stability. As an inert material, silica itself can effectively prevent the influence of the external environment on ammonium polyphosphate and prevent it from decomposing at high temperatures. The silica-coated ammonium polyphosphate powder forms a non-reactive physical barrier through the high temperature resistance of silica itself, thereby improving the ignition point and achieving flame retardancy. The silica-coated ammonium polyphosphate powder treated with phenol antioxidant has molecular clusters of phenol antioxidant on the surface of its silica layer. When the temperature is high enough, the phenol antioxidant can capture free radicals at high temperature, and the silica treated with the antioxidant will release the ammonium polyphosphate. After the ammonium polyphosphate is released, it decomposes and is captured by the phenol antioxidant. It forms a high-temperature resistant and oxygen-isolating protective film with the silica, which isolates oxygen and heat while increasing the ignition point, achieving a flame retardant effect, and also improves the thermal stability of the protective layer of the composite cross-linked polyethylene cable, extending its service life.
[0017] 3. The present invention prepares a composite cross-linked polyethylene cable protective layer by combining spherical rare earth nanomaterials with PE materials. The spherical rare earth nanomaterials composed of cerium ions, yttrium ions and stannates can improve the crystallinity and molecular chain arrangement of polyethylene after being added to the cross-linked polyethylene material, and act as a catalyst to promote the orderly arrangement of polyethylene molecular chains, accelerate the crystallization process, and change the crystallization kinetics of polyethylene, affecting the crystal transformation of polyethylene, making it easier to form a regular crystal structure. The regular crystal structure means that the grain arrangement is more orderly and dense, reducing the structural defects of internal vacancies and dislocations, and can better disperse stress when subjected to external pressure, thereby increasing the hardness and wear resistance of the surface of the cross-linked polyethylene material, making it more durable in a friction environment, which is manifested in improving its tensile strength, impact strength and elongation at break. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.
[0019] Figure 1 The present invention is a flow chart of a method for preparing a composite cross-linked polyethylene cable protective layer of a photoelectric composite cable that is resistant to tearing and wiring in a narrow space, as adopted in an embodiment of the present invention. DETAILED DESCRIPTION
[0020] The following is a detailed description of a photoelectric composite cable that is resistant to tearing in a narrow space provided by the present invention in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternatives to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.
[0021] Embodiment 1: A photoelectric composite cable that is resistant to breakage when laid in a narrow space, and a method for preparing a composite cross-linked polyethylene cable protective layer thereof, such as Figure 1 As shown, the following steps are included: S1: preparing spherical rare earth nanomaterials, comprising the following steps: S1.1: Weigh 100 parts by mass of cerium nitrate crystals and yttrium nitrate crystals, dissolve them in 200 parts by volume of deionized water, control the molar mass ratio of cerium atoms to yttrium atoms to be 97:3, stir them evenly with a magnetic stirrer, and obtain a mixed solution; S1.2: Sodium stannate trihydrate is added to the mixed solution, the molar mass ratio of n(Ce+Y):n(Sn) in the mixed solution is controlled to be 1:1, magnetic stirring is performed for 10 minutes to obtain a mixed ion solution, and the mixture is stirred at a speed of 1000 r / min. Under stirring, the mixed ion solution is mixed with 40 parts by volume of concentrated ammonia water, the mass fraction of the concentrated ammonia water is 25%, and then NaOH solution is added dropwise to adjust the pH value to 12; S1.3: Then continue stirring for 1 hour and transfer to the reactor. Use deionized water to adjust the solution volume to 75% of the reactor lining volume, and heat to 180°C and react for 12 hours. After the reaction is completed, naturally cool to room temperature 24°C, collect the precipitate by centrifugation and wash it with deionized water 3 times, and then place it in a vacuum drying oven at 100°C and dry it for 4 hours to obtain spherical rare earth nanomaterials.
[0022] S2: preparing silica-coated ammonium polyphosphate powder, comprising the following sub-steps: S2.1: 100 parts by mass of ammonium polyphosphate are added to 400 parts by mass of an ethanol aqueous solution, wherein the ethanol aqueous solution is prepared by mixing anhydrous ethanol and deionized water in a mass ratio of 2:1, and the solution is dispersed at a speed of 150 r / min for 5 minutes, and then the pH value is adjusted to 10 with ammonia water, and then 20 parts by mass of DMDES and 20 parts by mass of TEOS are added, and the solution is stirred at 50 r / min for 2 minutes, and the temperature is raised to 45°C while the stirring is maintained, and the solution is reacted for 2 hours to obtain a suspension; S2.2: The suspension was filtered, and the residue was washed with anhydrous ethanol for three times, then placed in a Soxhlet extractor and extracted with anhydrous ethanol for 20 hours, and finally placed in an electric heated blast drying oven at 80°C and dried for 20 hours to obtain silica-coated ammonium polyphosphate powder.
[0023] S3: Surface treatment of silica-coated ammonium polyphosphate powder, including the following sub-steps: S3.1: Add 65 parts by mass of silica-coated ammonium polyphosphate powder into a reaction bottle, add 200 parts by volume of anhydrous ethanol and 50 parts by volume of deionized water, and then add 0.65 parts by mass of silane coupling agent KH-560; S3.2: The reaction bottle was then fixed on a mechanical stirrer and reacted at 60°C for 1 hour. The filtrate was then filtered out and the solid was washed three times with anhydrous ethanol and dried in a drying oven at 80°C for 10 hours to obtain surface-modified silica-coated ammonium polyphosphate powder.
[0024] S4: preparing a composite cross-linked polyethylene cable protective layer, comprising the following sub-steps: S4.1: 2,6-di-tert-butylphenol and butyl diphenylamine were mixed in a mass ratio of 27:55, added to an equal mass of n-decane, and then benzoyl peroxide was added at 5% of the total mass of the system, and heated to 140°C and reacted for 2 hours to obtain an antioxidant; S4.2: 100 parts by mass of modified silica-coated ammonium polyphosphate powder, 2 parts by mass of triethylamine and 200 parts by mass of chloroform were added to a reaction bottle, heated to 45°C, stirred at 300 r / min for 5 min, and then 18 parts by mass of spherical rare earth nanomaterials and 5.7 parts by mass of antioxidant were added, reacted for 4 h, then cooled to 25°C, filtered, washed the solid product with water and chloroform respectively, and then dried at 80°C for 9 h to obtain a precursor powder; S4.3: Add 16% by mass of precursor powder, 5% of triazine macromolecular carbon-forming synergist and 78% of PE into the internal mixer, heat to 110°C, and stir at 40r / min until all are melted. Then add 0.6% of triallyl cyanate and 0.4% of diisopropyl peroxide, and then mix at 160°C for 15 minutes. Transfer to a twin-screw extruder and melt extrude at 180°C to obtain a composite cross-linked polyethylene cable protective layer.
[0025] The optical cables are bundled into cables and covered with the composite cross-linked polyethylene cable protective layer to obtain a photoelectric composite cable that is break-resistant and can be wired in a narrow space.
[0026] Embodiment 2: A photoelectric composite cable that is resistant to breakage when laid in a narrow space, and a method for preparing a composite cross-linked polyethylene cable protective layer thereof, such as Figure 1 As shown, the following steps are included: S1: preparing spherical rare earth nanomaterials, comprising the following sub-steps: S1.1: Weigh 100 parts by mass of cerium nitrate crystals and yttrium nitrate crystals, dissolve them in 250 parts by volume of deionized water, control the molar mass ratio of cerium atoms to yttrium atoms to be 98:2, and stir them evenly with a magnetic stirrer to obtain a mixed solution; S1.2: Sodium stannate trihydrate is added to the mixed solution, the molar mass ratio of n(Ce+Y):n(Sn) in the mixed solution is controlled to be 1:1.2, magnetic stirring is performed for 10 min to obtain a mixed ion solution, and the solution is stirred at a speed of 1000 r / min. Under stirring, the mixed ion solution is mixed with 40 parts by volume of concentrated ammonia water, the mass fraction of the concentrated ammonia water is 25%, and then NaOH solution is added dropwise to adjust the pH value to 12; S1.3: Then continue stirring for 1 hour and transfer to the reactor. Use deionized water to adjust the solution volume to 75% of the reactor lining volume, and heat to 180°C and react for 12 hours. After the reaction is completed, naturally cool to room temperature 24°C, collect the precipitate by centrifugation and wash it with deionized water 3 times, and then place it in a vacuum drying oven at 100°C and dry it for 4 hours to obtain spherical rare earth nanomaterials.
[0027] S2: preparing silica-coated ammonium polyphosphate powder, comprising the following sub-steps: S2.1: 110 parts by mass of ammonium polyphosphate are added to 420 parts by mass of an ethanol aqueous solution, wherein the ethanol aqueous solution is prepared by mixing anhydrous ethanol and deionized water in a mass ratio of 2:1.5, and dispersed at a speed of 150 r / min for 5 minutes, and then the pH value is adjusted to 10 with ammonia water, and then 25 parts by mass of DMDES and 25 parts by mass of TEOS are added, stirred at 50 r / min for 2 minutes, and the temperature is raised to 45°C while stirring, and reacted for 2 hours to obtain a suspension; S2.2: The suspension was filtered, and the residue was washed with anhydrous ethanol for three times, then placed in a Soxhlet extractor and extracted with anhydrous ethanol for 20 hours, and finally placed in an electric heated blast drying oven at 80°C and dried for 20 hours to obtain silica-coated ammonium polyphosphate powder.
[0028] S3: Surface treatment of silica-coated ammonium polyphosphate powder, including the following sub-steps: S3.1: Add 70 parts by mass of silica-coated ammonium polyphosphate powder into a reaction bottle, add 220 parts by volume of anhydrous ethanol and 60 parts by volume of deionized water, and then add 0.7 parts by mass of silane coupling agent KH-560; S3.2: The reaction bottle was then fixed on a mechanical stirrer and reacted at 60°C for 1 hour. The filtrate was then filtered out and the solid was washed three times with anhydrous ethanol and dried in a drying oven at 80°C for 10 hours to obtain surface-modified silica-coated ammonium polyphosphate powder.
[0029] S4: preparing a composite cross-linked polyethylene cable protective layer, comprising the following sub-steps: S4.1: 2,6-di-tert-butylphenol and butyl diphenylamine were mixed in a mass ratio of 30:65, added to an equal mass of n-decane, and then 8% of the total mass of benzoyl peroxide was added, and heated to 140°C and reacted for 2 hours to obtain an antioxidant; S4.2: 110 parts by mass of modified silica-coated ammonium polyphosphate powder, 2.5 parts by mass of triethylamine and 205 parts by mass of chloroform were added to a reaction bottle, heated to 45°C, stirred at 300 r / min for 5 min, and then 24 parts by mass of spherical rare earth nanomaterials and 6.8 parts by mass of antioxidant were added, reacted for 4 h, then cooled to 25°C, filtered, washed with water and chloroform respectively, and then dried at 80°C for 9 h to obtain a precursor powder; S4.3: Add 18% by mass of precursor powder, 6% of triazine macromolecular carbon-forming synergist and 74.6% of PE into the internal mixer, heat to 110°C, and stir at 40r / min until all are melted. Then add 0.8% of triallyl cyanate and 0.6% of diisopropyl peroxide, and then mix at 160°C for 15 minutes. Transfer to a twin-screw extruder and melt extrude at 180°C to obtain a composite cross-linked polyethylene cable protective layer.
[0030] The optical cables are bundled into cables and covered with the composite cross-linked polyethylene cable protective layer to obtain a photoelectric composite cable that is break-resistant and can be wired in a narrow space.
[0031] Embodiment 3: A photoelectric composite cable that is resistant to breakage when laid in a narrow space, and a method for preparing a composite cross-linked polyethylene cable protective layer thereof, such as Figure 1 As shown, the following steps are included: S1: preparing spherical rare earth nanomaterials, comprising the following sub-steps: S1.1: Weigh 100 parts by mass of cerium nitrate crystals and yttrium nitrate crystals, dissolve them in 200 parts by volume of deionized water, control the molar mass ratio of cerium atoms to yttrium atoms to be 97:3, stir them evenly with a magnetic stirrer, and obtain a mixed solution; S1.2: Sodium stannate trihydrate is added to the mixed solution, the molar mass ratio of n(Ce+Y):n(Sn) in the mixed solution is controlled to be 1:1, magnetic stirring is performed for 12 minutes to obtain a mixed ion solution, and the mixed ion solution is stirred at a speed of 1200 r / min. Under stirring, the mixed ion solution is mixed with 40 parts by volume of concentrated ammonia water, the mass fraction of the concentrated ammonia water is 25%, and then NaOH solution is added dropwise to adjust the pH value to 12.5; S1.3: Then continue stirring for 1 hour and transfer to the reactor. Use deionized water to adjust the solution volume to 75% of the reactor lining volume, and heat to 190°C and react for 12.5 hours. After the reaction is completed, naturally cool to room temperature 24°C, collect the precipitate by centrifugation and wash it with deionized water 3 times, and then place it in a vacuum drying oven at 110°C and dry it for 4 hours to obtain spherical rare earth nanomaterials.
[0032] S2: preparing silica-coated ammonium polyphosphate powder, comprising the following sub-steps: S2.1: 100 parts by mass of ammonium polyphosphate are added to 400 parts by mass of an ethanol aqueous solution, wherein the ethanol aqueous solution is prepared by mixing anhydrous ethanol and deionized water in a mass ratio of 2:1, and the mixture is dispersed at a speed of 200 r / min for 5 minutes, and then the pH value is adjusted to 10.5 with ammonia water, and then 20 parts by mass of DMDES and 20 parts by mass of TEOS are added, and the mixture is stirred at 100 r / min for 3 minutes, and the temperature is raised to 50°C while the stirring is maintained, and the reaction is carried out for 2.5 hours to obtain a suspension; S2.2: The suspension was filtered, and the residue was washed with anhydrous ethanol for three times, then placed in a Soxhlet extractor and extracted with anhydrous ethanol for 24 hours, and finally placed in an electric heated forced air drying oven at 85°C and dried for 24 hours to obtain silica-coated ammonium polyphosphate powder.
[0033] S3: Surface treatment of silica-coated ammonium polyphosphate powder, including the following sub-steps: S3.1: Add 65 parts by mass of silica-coated ammonium polyphosphate powder into a reaction bottle, add 200 parts by volume of anhydrous ethanol and 50 parts by volume of deionized water, and then add 0.65 parts by mass of silane coupling agent KH-560; S3.2: The reaction bottle was then fixed on a mechanical stirrer and reacted at 65°C for 1.5 hours. The filtrate was then filtered out and the solid was washed three times with anhydrous ethanol and dried in a drying oven at 85°C for 12 hours to obtain surface-modified silica-coated ammonium polyphosphate powder.
[0034] S4: preparing a composite cross-linked polyethylene cable protective layer, comprising the following sub-steps: S4.1: 2,6-di-tert-butylphenol and butyl diphenylamine were mixed in a mass ratio of 27:55, added to an equal mass of n-decane, and then benzoyl peroxide was added at 5% of the total mass of the system, and heated to 180°C and reacted for 3 hours to obtain an antioxidant; S4.2: 100 parts by mass of modified silica-coated ammonium polyphosphate powder, 2 parts by mass of triethylamine and 200 parts by mass of chloroform were added to a reaction bottle, heated to 50°C, stirred at 400 r / min for 10 min, and then 18 parts by mass of spherical rare earth nanomaterials and 5.7 parts by mass of antioxidant were added, reacted for 4.5 h, then cooled to 25°C, filtered, washed the solid product with water and chloroform respectively, and then dried at 85°C for 10 h to obtain a precursor powder; S4.3: Add 16% by mass of precursor powder, 5% of triazine macromolecular carbon-forming synergist and 78% of PE into the internal mixer, heat to 120°C, and stir at 60r / min until all are melted. Then add 0.6% of triallyl cyanate and 0.4% of diisopropyl peroxide, and then mix at 170°C for 20 minutes. Transfer to a twin-screw extruder and melt extrude at 200°C to obtain a composite cross-linked polyethylene cable protective layer.
[0035] The optical cables are bundled into cables and covered with the composite cross-linked polyethylene cable protective layer to obtain a photoelectric composite cable that is break-resistant and can be wired in a narrow space.
[0036] Comparative Example 1: Comparative Example 1 is a photovoltaic composite cable available on the market.
[0037] Comparative Example 2: Compared with Example 1, the difference of Comparative Example 2 is that no cerium nitrate is added in step S1.1, specifically: "S1.1: dissolving 97 parts by mass of cerium nitrate crystals in 200 parts by volume of deionized water, and stirring evenly with magnetic force to obtain a cerium nitrate solution; S1.2: Sodium stannate trihydrate is added to the cerium nitrate solution, and the molar mass ratio of n(Ce):n(Sn) in the cerium nitrate solution is controlled to be 1:1. The mixed ion solution is obtained by magnetic stirring for 10 minutes, and the solution is stirred at a speed of 1000 r / min. Under stirring, the mixed ion solution is mixed with 40 parts by volume of concentrated ammonia water, the mass fraction of which is 25%, and then NaOH solution is added dropwise to adjust the pH value to 12". The other steps remain unchanged. The prepared photoelectric composite cable that is resistant to wiring in a narrow space is recorded as Comparative Example 2.
[0038] Comparative Example 3: Compared with Example 1, the difference of Comparative Example 3 is that no yttrium nitrate is added in step S1.1, specifically: “S1.1: dissolving 3 parts by mass of cerium nitrate crystals in 200 parts by volume of deionized water, and stirring evenly with magnetic force to obtain a cerium nitrate solution; S1.2: Sodium stannate trihydrate is added to the cerium nitrate solution, and the molar mass ratio of n(Y):n(Sn) in the cerium nitrate solution is controlled to be 1:1. The mixed ion solution is obtained by magnetic stirring for 10 minutes, and the solution is stirred at a speed of 1000 r / min. Under stirring, the mixed ion solution is mixed with 40 parts by volume of concentrated ammonia water, the mass fraction of which is 25%, and then NaOH solution is added dropwise to adjust the pH value to 12". The other steps remain unchanged. The prepared photoelectric composite cable that is resistant to wiring in a narrow space is recorded as Comparative Example 3.
[0039] Comparative Example 4: Compared with Example 1, the difference of Comparative Example 4 is that step S4.1 is not performed, and no antioxidant is added in step S4.2, specifically: "S4: preparing a composite cross-linked polyethylene cable protective layer, comprising the following sub-steps: S4.1: 100 parts by mass of silica-coated ammonium polyphosphate powder, 2 parts by mass of triethylamine and 200 parts by mass of chloroform are added to a reaction bottle, heated to 45°C, stirred at 300 r / min for 5 min, and then 18 parts by mass of spherical rare earth nanomaterials are added, reacted for 4 hours, then cooled to 25°C, filtered, washed with water and chloroform respectively, and then dried at 80°C for 9 hours to obtain a precursor powder; ", the other steps remain unchanged, and the prepared optoelectronic composite cable that is resistant to wiring in a narrow space is recorded as Comparative Example 4.
[0040] Comparative Example 5: Compared with Example 1, the difference of Comparative Example 5 is that in step S4.3, no precursor powder is added, but it is replaced by modified silica-coated ammonium polyphosphate powder, specifically: "S4.3: Add 16% by mass of modified silica-coated ammonium polyphosphate powder, 5% of triazine macromolecular carbon-forming synergist and 78% of PE into the internal mixer, heat to 110°C, and stir at 40r / min until all melted, then add 0.6% of triallyl cyanate and 0.4% of diisopropylbenzene peroxide, and then mix at 160°C for 15 minutes, transfer to a twin-screw extruder, and melt extrude at a temperature of 180°C to obtain a composite cross-linked polyethylene cable protective layer", and the other steps remain unchanged. The prepared optoelectronic composite cable that is resistant to wiring in a narrow space is recorded as Comparative Example 5.
[0041] The tensile strength, elongation at break, limiting oxygen index and high temperature pressure crack resistance of Examples 1-3 and Comparative Examples 1-5 were tested. The test results are shown in Tables 1 and 2.
[0042] Table 1
[0043] Table 2
[0044] The tensile strength and elongation at break of Examples 1-3 are higher than those of Comparative Example 1, and the limiting oxygen index of the examples is also higher than that of the comparative example. The higher the tensile strength and the elongation at break, the greater the pressure the cable can withstand. The limiting oxygen index is generally used to indicate the flame retardant properties of the cable. The higher the limiting oxygen index, the more difficult it is for the cable to burn. In a small space, it is easy for the cable to burn due to local high temperatures caused by densely packed cables. Therefore, the cable has better flame retardant properties and is more suitable for wiring in a small space. In addition, no cracks were found in the examples in the high-temperature pressure crack resistance test, indicating that the cable has better crack resistance.
[0045] The tensile strength of Comparative Example 1 is 12.5 MPa, the elongation at break is 236%, and the limiting oxygen index is 36%, all of which are weaker than those of the embodiment, and cracking occurs in the high-temperature pressure anti-cracking test. It can be seen that the optoelectronic composite cable prepared by the present invention has better tensile strength and anti-cracking performance than commercially available products.
[0046] The tensile strength of Comparative Example 2 is 12.2 MPa, and the elongation at break is 214%. The tensile strength of Comparative Example 3 is 12.7 MPa, and the elongation at break is 194%. Its limiting oxygen index is also lower than that of the embodiment, and cracking occurs in the high-temperature pressure anti-cracking test. It can be seen that the spherical rare earth nanomaterial prepared by combining yttrium nitrate and cerium nitrate can improve the tensile properties and anti-cracking properties of the cable when added to the cross-linked polyethylene material, while the single yttrium nitrate or the prepared material does not have better performance.
[0047] The tensile strength of Comparative Example 4 is 12.3 MPa, the elongation at break is 231%, the limiting oxygen index is 26%, and cracking occurs in the high temperature pressure anti-cracking test. Its tensile strength and elongation at break are similar to those of commercially available products, but the limiting oxygen index is greatly reduced. It can be seen that only the silica-coated ammonium polyphosphate powder treated with an antioxidant has better flame retardancy and thermal stability for improving the protective layer of the composite cross-linked polyethylene cable. If there is no antioxidant combined with the silica in the silica-coated ammonium polyphosphate powder, its flame retardancy will be significantly reduced.
[0048] The tensile strength of Comparative Example 5 is 10.8 MPa, the elongation at break is 223%, the limiting oxygen index is 30%, and cracking occurs in the high temperature pressure cracking resistance test. It can be seen that the combination of spherical rare earth nanomaterials and PE materials significantly improves the physical properties of polyethylene cross-linked materials such as wear resistance and compression resistance. The tensile strength and elongation at break values are much smaller than those of the embodiments, and the limiting oxygen index also decreases accordingly. It can be seen that its poor physical properties also affect the thermal stability and flame retardant properties.
[0049] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A photoelectric composite cable that is resistant to damage when laid in a narrow space, characterized in that: The photoelectric composite cable that is resistant to being wired in a narrow space comprises a composite cross-linked polyethylene cable protective layer and an optical cable, wherein the composite cross-linked polyethylene cable protective layer comprises the following components: The mass percentages are 16-18% of precursor powder, 5-6% of carbonizing agent, 74.6-78% of PE, 0.6-0.8% of triallyl cyanate and 0.4-0.6% of diisopropylbenzene peroxide; the preparation method of the composite cross-linked polyethylene cable protective layer is as follows: the precursor powder, the carbonizing agent and PE are added into an internal mixer, heated and stirred, then triallyl cyanate and diisopropylbenzene peroxide are added, mixed, transferred into a twin-screw extruder, melt-extruded, and the composite cross-linked polyethylene cable protective layer is obtained; The preparation method of the precursor powder is as follows: 100-110 parts by weight of silica-coated ammonium polyphosphate powder, 2-2.5 parts by weight of triethylamine and 200-205 parts by weight of chloroform are added to a reaction bottle, heated to 45-50° C., stirred at 300-400 r / min for 5-10 minutes, and then 18-24 parts by weight of spherical rare earth nanomaterials and 5.7-6.8 parts by weight of antioxidant are added, reacted for 4-4.5 hours, then cooled to 25° C., filtered, washed the solid product with water and chloroform respectively, and then dried at 80-85° C. for 9-10 hours to obtain the precursor powder; The preparation method of the spherical rare earth nanomaterial comprises: weighing cerium nitrate crystals and yttrium nitrate crystals, dissolving them in deionized water, stirring them evenly with a magnetic force to obtain a mixed solution, weighing sodium stannate trihydrate, adding them to the mixed solution, stirring them magnetically to obtain a mixed ion solution, and mixing the mixed ion solution with concentrated ammonia water, then continuing to stir, heating, centrifuging, collecting precipitates, and drying them to obtain the spherical rare earth nanomaterial; The preparation method of the antioxidant is as follows: 2,6-di-tert-butylphenol and butyl diphenylamine are mixed in a mass ratio of (27-30): (55-65), and then added into an equal mass of n-decane, and then 5-8% of the total mass of the system is added with benzoyl peroxide, and the mixture is heated to 140-180° C. and reacted for 2-3 hours to obtain the antioxidant.
2. The photoelectric composite cable according to claim 1, which is resistant to breakage when laid in a narrow space, is characterized in that: The method for preparing the composite cross-linked polyethylene cable protective layer comprises the following steps: S1: preparing spherical rare earth nanomaterials: weighing cerium nitrate crystals and yttrium nitrate crystals, dissolving them in deionized water, and stirring them evenly with a magnetic stirrer to obtain a mixed solution, weighing sodium stannate trihydrate, adding them to the mixed solution, and stirring them magnetically to obtain a mixed ion solution, and mixing the mixed ion solution with concentrated ammonia water, and then continuing to stir, heat, centrifuge, collect the precipitate, and dry it to obtain a spherical rare earth nanomaterial; S2: preparing silica-coated ammonium polyphosphate powder: adding ammonium polyphosphate into an ethanol aqueous solution, dispersing, then adding DMDES and TEOS, stirring, reacting to obtain a suspension, filtering the suspension, and drying to obtain silica-coated ammonium polyphosphate powder; S3: Surface treatment of silica-coated ammonium polyphosphate powder: Add silica-coated ammonium polyphosphate powder into a reaction bottle, add anhydrous ethanol and deionized water, and then add silane coupling agent KH-560, stir, then filter to remove the filtrate, wash the solid with anhydrous ethanol, and dry to obtain modified silica-coated ammonium polyphosphate powder; S4: Preparation of composite cross-linked polyethylene cable protective layer: Mix 2,6-di-tert-butylphenol and butyldiphenylamine and add to n-decane, then add benzoyl peroxide and heat to obtain an antioxidant, add modified silica-coated ammonium polyphosphate powder, triethylamine and chloroform to a reaction bottle, heat and stir, then add spherical rare earth nanomaterials and antioxidants, react, filter, wash the solid product, dry to obtain a precursor powder, add the precursor powder, carbon-forming agent and PE to an internal mixer, heat and stir, then add triallyl cyanate and diisopropyl peroxide, mix, transfer to a twin-screw extruder, melt extrude to obtain a composite cross-linked polyethylene cable protective layer.
3. The photoelectric composite cable according to claim 2, which is resistant to breakage when laid in a narrow space, is characterized in that: In the method for preparing the composite cross-linked polyethylene cable protective layer, step S1 of preparing spherical rare earth nanomaterials comprises the following steps: S1.1: Weigh 99-101 parts by mass of cerium nitrate crystals and yttrium nitrate crystals, dissolve them in 200-250 parts by volume of deionized water, control the molar mass ratio of cerium atoms to yttrium atoms to be (97-98):(2-3), stir magnetically to obtain a mixed solution; S1.2: adding sodium stannate trihydrate to the mixed solution, controlling the molar mass ratio of n(Ce+Y):n(Sn) in the mixed solution to be 1:(1-1.2), magnetically stirring for 10-12 minutes to obtain a mixed ion solution, and stirring at a speed of 1000-1200 r / min, mixing the mixed ion solution with 40-45 parts by volume of concentrated ammonia water under stirring, and then dropping NaOH solution to adjust the pH value to 12-12.5; S1.3: Then continue stirring for 1-1.5 hours and then transfer to a reactor. Use deionized water to adjust the solution volume to 75-80% of the reactor lining volume, and heat to 180-190°C and react for 12-12.5 hours. After the reaction is completed, naturally cool to room temperature 24°C, collect the precipitate by centrifugation, wash it 3 times with deionized water, and then place it in a vacuum drying oven at 100-110°C and dry it for 4-4.5 hours to obtain spherical rare earth nanomaterials.
4. The photoelectric composite cable according to claim 2, which is resistant to breakage when laid in a narrow space, is characterized in that: In the method for preparing the composite cross-linked polyethylene cable protective layer, step S2 is to prepare silicon dioxide-coated ammonium polyphosphate powder, comprising the following steps: S2.1: 100-110 parts by weight of ammonium polyphosphate is added to 400-420 parts by weight of ethanol aqueous solution, and dispersed at a speed of 150-200 r / min for 5-10 minutes, and then the pH value is adjusted to 10-10.5 with ammonia water, and then 20-25 parts by weight of DMDES and 20-25 parts by weight of TEOS are added, and stirred at 50-100 r / min for 2-3 minutes, and the temperature is raised to 45-50°C while stirring, and the reaction is carried out for 2-2.5 hours to obtain a suspension; S2.2: The suspension is filtered, and the filter residue is washed with anhydrous ethanol for three times, then placed in a Soxhlet extractor and extracted with anhydrous ethanol for 20-22 hours, and finally placed in an electric heated forced air drying oven at 80-85°C and dried for 20-24 hours to obtain silica-coated ammonium polyphosphate powder.
5. The photoelectric composite cable that is resistant to breakage when wiring in a narrow space according to claim 2, characterized in that: In the method for preparing the composite cross-linked polyethylene cable protective layer, step S3, surface treatment of the silica-coated ammonium polyphosphate powder, comprises the following steps: S3.1: Add 65-70 parts by mass of silica-coated ammonium polyphosphate powder into a reaction bottle, add 200-220 parts by volume of anhydrous ethanol and 50-60 parts by volume of deionized water, and then add 0.65-0.7 parts by mass of silane coupling agent KH-560; S3.2: The reaction bottle is then fixed on a mechanical stirrer and reacted at 60-65°C for 1-1.5 hours. The filtrate is then filtered to remove the filtrate. The solid is washed three times with anhydrous ethanol and placed in a drying oven at 80-85°C for 10-12 hours to obtain surface-modified silica-coated ammonium polyphosphate powder.
6. The photoelectric composite cable that is resistant to breakage when wiring in a narrow space according to claim 2, characterized in that: In the method for preparing the composite cross-linked polyethylene cable protective layer, step S4 of preparing the composite cross-linked polyethylene cable protective layer comprises the following steps: S4.1: 2,6-di-tert-butylphenol and butyl diphenylamine are mixed in a mass ratio of (27-30):(55-65), and then added to an equal mass of n-decane, and then 5-8% of the total mass of benzoyl peroxide is added, and the mixture is heated to 140-180°C and reacted for 2-3 hours to obtain an antioxidant; S4.2: Add 100-110 parts by weight of silica-coated ammonium polyphosphate powder, 2-2.5 parts by weight of triethylamine and 200-205 parts by weight of chloroform into a reaction bottle, heat to 45-50°C, stir at 300-400 r / min for 5-10 min, then add 18-24 parts by weight of spherical rare earth nanomaterials and 5.7-6.8 parts by weight of antioxidant, react for 4-4.5 h, then cool to 25°C, filter, wash the solid product with water and chloroform respectively, and then dry at 80-85°C for 9-10 h to obtain a precursor powder; S4.3: Add 16-18% by mass of precursor powder, 5-6% of carbonizing agent and 74.6-78% of PE into the internal mixer, heat to 110-120°C, and stir at a speed of 40-60r / min until all melted, then add 0.6-0.8% of triallyl cyanate and 0.4-0.6% of diisopropyl peroxide, and then mix at 160-170°C for 15-20min, transfer to a twin-screw extruder, and melt extrude at a temperature of 180-200°C to obtain a composite cross-linked polyethylene cable protective layer.
7. The photoelectric composite cable that is resistant to breakage when wiring in a narrow space according to claim 3, characterized in that: In the method for preparing the composite cross-linked polyethylene cable protective layer, the mass fraction of concentrated ammonia water in step S1.3 is 25-30%.
8. The photoelectric composite cable that is resistant to breakage when wiring in a narrow space according to claim 4, characterized in that: In the method for preparing the composite cross-linked polyethylene cable protective layer, the ethanol aqueous solution in step S2.1 is prepared by mixing anhydrous ethanol and deionized water in a mass ratio of 2: (1-1.5).
9. The photoelectric composite cable that is resistant to breakage when wiring in a narrow space according to claim 6, characterized in that: The carbon-forming agent in step S4.3 of the method for preparing the composite cross-linked polyethylene cable protective layer is specifically a triazine macromolecular carbon-forming synergist.
10. The photoelectric composite cable that is resistant to breakage when wiring in a narrow space according to claim 2, characterized in that: The preparation method of the photoelectric composite cable that is resistant to tearing when wiring in a narrow space is to bundle optical cables into cables and cover them with the composite cross-linked polyethylene cable protective layer to obtain the photoelectric composite cable that is resistant to tearing when wiring in a narrow space.
Citation Information
Patent Citations
Halogen-free flame-retardant heat-resistant cable material and preparation method thereof
CN114276608A
Method for preparing core-shell silicon dioxide-coated ammonium polyphosphate (APP)
CN101760049A
Low-smoke halogen-free flame-retardant antistatic aging-resistant wire and cable material and its preparation method
CN102477178A
Preparation method and use of yttrium-doped bismuth stannate nanocrystallines
CN104941627A
High-temperature anti-oxidant for lubricating oil and preparation method of high-temperature anti-oxidant
CN105038904A